1998
DOI: 10.1152/ajplung.1998.275.3.l574
|View full text |Cite
|
Sign up to set email alerts
|

Store-operated calcium entry promotes shape change in pulmonary endothelial cells expressing Trp1

Abstract: Activation of Ca2+ entry is known to produce endothelial cell shape change, leading to increased permeability, leukocyte migration, and initiation of angiogenesis in conduit-vessel endothelial cells. The mode of Ca2+ entry regulating cell shape is unknown. We hypothesized that activation of store-operated Ca2+ channels (SOCs) is sufficient to promote cell shape change necessary for these processes. SOC activation in rat pulmonary arterial endothelial cells increased free cytosolic Ca2+ that was dependent on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 33 publications
7
113
1
Order By: Relevance
“…The mechanism by which Src regulates Ca 2+ influx is unclear. Src may phosphorylate plasma membrane transient receptor potential channels expressed in endothelial cells [119,120] that mediate Ca 2+ influx during inositol trisphosphate-sensitive intracellular store depletion [121,122]. Thrombin increased the tyrosine phosphorylation of junctional proteins and the formation of interendothelial gaps that are characteristically associated with the loss of barrier function [2,11,66,67,123].…”
Section: Thrombinmentioning
confidence: 99%
“…The mechanism by which Src regulates Ca 2+ influx is unclear. Src may phosphorylate plasma membrane transient receptor potential channels expressed in endothelial cells [119,120] that mediate Ca 2+ influx during inositol trisphosphate-sensitive intracellular store depletion [121,122]. Thrombin increased the tyrosine phosphorylation of junctional proteins and the formation of interendothelial gaps that are characteristically associated with the loss of barrier function [2,11,66,67,123].…”
Section: Thrombinmentioning
confidence: 99%
“…It is very probable that more than one type of TRP channel is expressed in ASM. Indeed, both TRP6 and TRP7 have been found in lung (Boulay et al, 1997;Moore et al, 1998;Okada et al, 1999), while TRP1 has been shown to regulate endothelial permeability in the pulmonary vasculature (Moore et al, 1998).…”
Section: British Journal Of Pharmacology Vol 133 (2)mentioning
confidence: 99%
“…However, it has been previously argued that mammalian homologs of the transient receptor potential (TRP) gene family and notably the canonical TRPC subfamily of channels function as SOCs (43). Thus both TRPC1 and TRPC4 have been implicated in mediating SOCE in endothelial cells (23,34). Indeed, TRPC1 has been shown to colocalize with Orai1 and STIM1, and studies with exogenously expressed TRPC1 and STIM1 in endothelial cells indicate that TRPC1 is regulated by STIM1 (26,38).…”
mentioning
confidence: 99%